On Occasion of the Public Defence of the Dissertation: Thought in Image: Søren Kierkegaards Poetics - Holm, Isak Winkel (KIERKEGAARDIANA, 1999)
On Occasion of the Public Defence of the Dissertation: Thought in Image: Søren Kierkegaards Poetics